Operational weather forecasting - Inness, Peter (Peter M.); Dorling, Steve (Stephen R.) (Hoboken, N.J. : John Wiley & Sons, Ltd, 2013)
"This book will cover the end-to-end process of operational weather forecasting"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Weather forecasting; Electronic books